Antifungal Susceptibility of Dermatophytes - María Teresa Colella; María Castro; Marvia Montiel; Erika Vásquez; Sofía Mata-Essayag; Sylvia Magaldi; Claudia Hartung de Capriles; Celina Pérez; Carolina Olaizola; Roselló Arántza (Kasmera, 2006)
There are no test standarizaded for the antifungal susceptibility of dermatophytes. The aim of this study is to probe the well diffusion technique as antifungal susceptibility test for dermatophites. One hundred species of dermatophytes were isolated and identified (74 Trichophyton rubrum, 18 Trichophyton mentagrophytes, 1 Trichophyton tonsurans, 5 Microsporum canis and 2 Epidermophyton floccosum).in the Medical Micology Departament of TMI. The antifungal sensitivity of the isolates of the dermatophytes to the drugs was carried out using the well diffusion technique. The antifungal agents tested were griseofulvin, terbinafine, itraconazole and fluconazole. Results were interpreted according to NCCLS breakpoints. The inoculum suspension was standardized by weight measurement. Agar Staib was considered the most suitable, because 97% of the isolates grew on it. This is the first time the inoculum suspension of dermatophytes is standardized by weight measurement. Terbinafine was found to be the most effective drug, followed by Griseofulvin and Itraconazole. Fluconazole were not found to be effective.